PERLINDUNGAN HUKUM KONSUMEN DALAM JUAL BELI EMAS MELALUI INFORMASI DAN TRANSAKSI ELEKTRONIK - Ufuk Yoko Wibowo; Made Warka (Gapenas Publisher, 2022)
Development in Research and Technologies brought us to the next chapter of trading behaviour, which known as online transaction. Gold can be the media of trading without real submission between seller and dealer. With a piece of paper, this new method of economics struggling in human industry can be start with a very tiny pieces, 0.01 gram. These brand-new ideas are tried to be understood in Indonesian Legal Constitution as a guidance in status quo